O testemunho no ensino de história : a lembrança, o esquecimento e o sensível - Indicatti, Kelen Katlen Staehler (My University, 2018)
This study presents an approach on the testimony used as a source in teaching the history of the World War II. Its object of analysis is a project with survivors of the Shoah, developed by the Marc Chagall Institute. Through oral history, memory and testimony, it enabled the development of a didactic sequence that promotes sensitization, human learning and meaningful relation to the traumatic history of the war. The product elaborated by this research constitutes, then, in a material of reference for the teacher to use the panel on Shoah in basic education.
Este estudo apresenta uma abordagem sobre o testemunho utilizado como fonte no ensino da história da Segunda Guerra Mundial. Tem como objeto de análise um projeto com sobreviventes da Shoah, desenvolvido pelo Instituto Marc Chagall. Por meio da história oral, da memória e do testemunho, possibilitou o desenvolvimento de uma sequência didática que promove a sensibilização, a aprendizagem humana e significativa em relação a história traumática da guerra. O produto elaborado por esta pesquisa constitui-se, então, em um material de referência para o professor utilizar o painel sobre a Shoah na educação básica.
Keywords: História - Estudo e ensino; História oral; Holocausto judeu (1939-1945); History -Study and teaching; Oral history; Holocaust, Jewish (1939-1945)